2013
DOI: 10.1021/jp3113232
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-Plane Dependence of Critical Concentration for Nucleation on Hydrothermal ZnO Nanowires

Abstract: Hydrothermal ZnO nanowires have shown great potential for various nanoscale device applications due to their fascinating properties and lowtemperature processing. A preferential crystal growth of ZnO (0001) polar plane is essential and fundamental to realize the anisotropic nanowire growth. Here we demonstrate that a critical concentration for a nucleation strongly depends on a crystal plane, which plays an important role on an anisotropic growth of hydrothermal ZnO nanowires. We measure a growth rate of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 53 publications
(85 reference statements)
3
74
1
Order By: Relevance
“…Up to now, electrical properties of a bottom-up nanocrystal and its device properties are reported assuming electrical uniformities. However, this is idealistic because each crystallographic plane surface has an atomic arrangement with unique chemical activity (for example, etching rate 12 13 , host crystal growth rate 14 15 and incorporation rates of point-defects), as is reported on plane-dependent donor concentration in ZnO bulk crystal 13 16 and amphoteric Si-doping in GaAs substrates 17 18 . Thus, a nanocrystal grown in multiple crystallographic orientations has corresponding growth sectors with different electric properties, which is critical for above electronic applications.…”
mentioning
confidence: 99%
“…Up to now, electrical properties of a bottom-up nanocrystal and its device properties are reported assuming electrical uniformities. However, this is idealistic because each crystallographic plane surface has an atomic arrangement with unique chemical activity (for example, etching rate 12 13 , host crystal growth rate 14 15 and incorporation rates of point-defects), as is reported on plane-dependent donor concentration in ZnO bulk crystal 13 16 and amphoteric Si-doping in GaAs substrates 17 18 . Thus, a nanocrystal grown in multiple crystallographic orientations has corresponding growth sectors with different electric properties, which is critical for above electronic applications.…”
mentioning
confidence: 99%
“…To understand the contribution of WO 4 2− ions for the nucleation phenomenon, next we examine the Zn precursor concentration dependence on ZnO nanowire growth with various C W . Previous our study demonstrated that there exist two threshold concentrations corresponding to the critical concentrations for nucleation on (0001) plane and 10 10 ð Þ plane [22][23][24] . By evaluating the shifts of critical concentrations with varying C W , the influence of WO 4 2− ions for the nucleation events on ZnO crystal planes can be identified.…”
Section: Resultsmentioning
confidence: 76%
“…In principle, there are two possible approaches for modulating the dopant incorporation, i.e., a control of W precursor concentration and a control of dopant adsorption on nanowire surface. On the other hand, the morphology can be manipulated by controlling C Zn according to the critical concentration for nucleation on ZnO crystal planes, which is so-called as "concentration window" principle [22][23][24] . However, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the substrate with the microchannel having the ZnO layer was immersed into the nanowire hydrothermal growth solution (40 mL), which was a mixture of 40 mM hexamethylenetetramine (HMTA, Wako Pure Chemical Industries, Ltd.) and 40 mM zinc nitrate hexahydrate (Thermo Fisher Scientific Inc.); this mixture was heated at 95°C for 3 hours. 37,38 After washing with pure water, an Au layer was sputtered on the ZnO nanowires to obtain SAM. The Au sputtering at a rate of 89 nm min −1 on a flat substrate was performed for 60 s. The positive photoresist layer was removed by immersing the substrate with the Au-coated nanowires and microchannel into Strip-per104 (Tokyo Ohka Kogyo Co., Ltd.) at 75°C for 30 min.…”
Section: Fabrication Of Mpc-sh Sam-modified Nanowires Inside a Microcmentioning
confidence: 99%